Ekonomi Islam sebagai Landasan Fundamental dalam Praktik Bisnis Online Era Digital - Sain, Muhammad; Bahri, Samsul (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
This study aims to explore the relationship between technological innovation and sharia values, focusing on how aspects of digital transactions such as transparency, fairness, and consumer rights protection can be integrated into modern business practices. Using a literature study method, this study concludes that Islamic economics as a fundamental foundation offers an essential ethical and moral framework for online business practices in the digital era, emphasizing the importance of integrity, fairness, and transparency in every transaction. Sharia principles—which prohibit usury, injustice, monopoly, and fraud—serve as a guide to creating a digital trading ecosystem that prioritizes not only financial gain but also social and moral welfare. By implementing these values, online businesses can operate with responsibility and credibility, build trust among market players and consumers, and ensure that technological innovation remains in line with the principles of justice and ethics that underlie Islamic law. This integration is not only a legal compliance, but also an effort to create harmony between digital progress and the noble values ​​that guide economic activities towards sustainability and justice.